Edukasi dan Implementasi Teknik Nafas Dalam pada Pasien Sectio Caesarea terhadap Penurunan Mual dan Muntah saat Intra Anestesi di RSUD Ajibarang - Nashya, Jhea Aqilla; Yudha, Magenda Bisma; Triana, Noor Yunida (Lembaga Yasin AlSys, 2025)
Intraoperative nausea and vomiting (IONV) is a common complication during sectio caesarea procedures under spinal anesthesia, primarily caused by hypotension resulting from sympathetic nerve blockade and vasodilation. This study aims to evaluate the effectiveness of deep breathing techniques in reducing the incidence of IONV among sectio caesarea patients at Ajibarang Regional General Hospital. A quasi-experimental quantitative method was employed, involving 30 respondents undergoing cesarean section. The intervention consisted of education and demonstration of deep breathing techniques administered before and after anesthesia. Data were collected using the Apfel Score to assess IONV risk and direct observation of nausea and vomiting events. The results showed that prior to the intervention, 70% of respondents experienced IONV, whereas after implementing the deep breathing technique, 96.7% of respondents did not experience nausea or vomiting. This significant reduction indicates that deep breathing is effective as a non-pharmacological method for minimizing complications during the intraoperative phase. The study concludes that deep breathing is a simple, cost-effective, and practical approach for reducing IONV, and it is recommended as part of perioperative nursing interventions. The implications support broader clinical adoption and integration into obstetric anesthesia protocols.